MORAL VALUES IN JUSTIN ZACKHAM’S MOVIE SCRIPT THE BUCKET LIST - Fitri Marini; Pardi Pardi (JOURNAL OF LANGUAGE, 2022)
Justin Zackham published the script for his film The Bucket List in 2007. The script tells the story of two men who have serious illnesses and have a strong desire to continue doing things they haven't done before they die. The film script was adopted into a film in 2008. This study aims to reveal the moral values contained in the film script. Various theories related to moral values were adopted to support this analysis, but the main theory that will be used is the theory proposed by Berterns. Another concept is proposed by Elizabeth stating that moral is controlled by the moral, the rules of moral to which the members of a culture have become accustomed to and which determine the expected behavior pattern of all group members. The method used in this study is a qualitative descriptive method. The results of the analysis show that the moral values found in the characters discussed, Edward Cole and Carter Chambers, are the values of courage, honesty, patience, responsibility, and humility. These moral values make the two characters successful and useful for many people.